Cross-Sectional Study: Family Social Support and Self-Harm Behavior in Early Adolescents in the Agricultural Region of Jember Regency - Hamzah, Rizqi Bachtiar; Fitria, Yeni; Kurniyawan, Enggal Hadi; Dewi, Erti Ikhtiarini; Deviantony, Fitrio (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Problems experienced by early adolescents are often triggered by stressors related to physical, cognitive, and emotional changes, which may lead to low self-confidence and self-harming behaviors. These issues can cause psychological distress, thereby increasing the importance of family support. This study aimed to analyze the relationship between family social support and self-harm behavior among early adolescents in the agricultural region of Jember Regency. A correlational research design with a cross-sectional approach was employed. The study population consisted of early adolescents enrolled in public junior high schools (SMPN) in Jember, totaling 2,191 students. A sample of 376 students was selected using proportionate stratified random sampling. Data were collected using the Perceived Social Support from Family (PSS-Fa) questionnaire and the Deliberate Self-Harm Inventory (DSHI). Bivariate statistical analysis using Kendall’s tau-C revealed a significant relationship between family social support and self-harm behavior in early adolescents in the agricultural region of Jember (p = 0.002, r = -0.081). These findings indicate that family social support plays a crucial role in maintaining adolescents' emotional stability and preventing self-harm behaviors resulting from difficulties in adapting to stressors.